Gestión de procesos creativos aplicados al desarrollo de proyectos de personal branding. - Manzano Lescano, Sebastián Salvador (2023)
Currently, the development of personal brands ¡in the province of Pastaza 18 non existent, only brand creations have been made for companies or organizations empirically without an adequate technical study development, so the objective of the work carried out 1s to analyze the processes of creative management applied to the development of personal branding projects; for which the Design Thinking methodology proposed by Tim Brown was applied, which consists of five phases (empathize, define, devise, prototype and test) that were developed according to the case study (professional of the environmental engineering career), obtaining as a result a creative management process according to the aforementioned methodology (briefing, BenchMark, visual branding canvas, sketching, value scales, surveys) which were generated through a focus group itself that helped the generated proposal have a focus technical. At the same time, a brand manual, a media plan and a post timetable were developed.